GOVERNMANT PARTICIPATION IN IMPROVING THE QUALITY OF RELIGIOUS TEACHERS IN INDONESIA - Zailani Zailani; Arif Prasetio; Sukriadi Bancin; Muhammad Dicky (Proceeding International Seminar of Islamic Studies, 2021)
One of the most important issues regarding education in Indonesia is about educators, especially Islamic educators. In terms of teacher education, it is an important figure in improving the quality of students, to achieve quality students, of course a teacher also has quality, especially religion teachers in Indonesia. . One of the policies that have been made by the commitment of the Indonesian government in improving the quality of teachers, especially religion teachers in Indonesia, is listed in PP NO. 19 of 2005 on National Education Standards chapter VI and PP RI NO. 19 of 2005 on National Education Standards, chapter VI article 28 paragraph (3) and PP NO. 19 of 2005 on National Education Standards chapter VI and PP RI NO. 19 of 2005 on National Education Standards, chapter VI, article 28 paragraph (3). The purpose of this study is to determine the development of the quality of religious teachers in Indonesia through policies made by the government. The method used in this research is descriptive and quantitative methods. And it is hoped that with this regulation from the government the quality of religious teachers, especially Islamic education religion teachers, can increase rapidlyKeywords : The Role of Government, Quality of Islamic Religious Education